Challenges in the Construction of the Crystal Houses Façade - F. Oikonomopoulou (Challenging Glass Conference, 2016)
This paper presents the main challenges confronted during the construction of the innovative Crystal Houses façade in Amsterdam. Designed by MVRDV and Gietermans & Van Dijk architectural offices, the façade is a transparent reproduction of the previous 19th century masonry elevation, entirely made of adhesively bonded solid glass bricks. Even the window and door frames are reinterpreted by elaborated massive cast glass components. To obtain pure transparency, the resulting 10 m by 12 m glass masonry wall should be self-supporting. To achieve the desired structural performance of the wall a colourless UV-curing adhesive of high stiffness is selected which reaches its optimum bond strength when applied in 0.3mm thick layer. The virtually zero thickness of the adhesive and the desire of untainted transparency induced various engineering challenges, from the adhesive’s homogeneous application and the dimensional accuracy of the bricks to the allowable tolerances in the entire façade. This paper records the challenges encountered and follows the innovations made from the manufacturing of the bricks to the final construction of the façade. The novel solutions include the manufacturing of glass elements of extreme dimensional precision, the development of methods for the accurate measuring and systematic levelling of the façade and the development of customized bonding techniques that lead to purely transparent and flawless connections. Based on the conclusions of the research and experience gained from the realization of the project, suggestions are made on the optimization of the developed system for its further applicability.